2018
DOI: 10.1242/jeb.177303
|View full text |Cite
|
Sign up to set email alerts
|

First demonstration of olfactory learning and long term memory in honey bee queens

Abstract: As the primary source of colony reproduction, social insect queens play a vital role. However, the cognitive abilities of queens are not well understood, although queen learning and memory are essential in multiple species such as honey bees, in which virgin queens must leave the nest and then successfully learn to navigate back over repeated nuptial flights. Honey bee queen learning has never been previously demonstrated. We therefore tested olfactory learning in queens and workers and examined the role of DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
(105 reference statements)
1
9
0
Order By: Relevance
“…DesJardins and Tibbetts (2018) studied P. fuscatus workers and males (drones) over a wide age range (5-30 days) and found that workers were consistently better at facial learning, but the two castes were equally good at colour learning. Similarly, Gong et al (2018) reported that the proportion of honey bee queens (Apis mellifera) exhibiting learning was 5-fold higher than that of honey bee workers at every tested age (5-25 days). Finally, it is possible that workers had decreased learning ability as a result of senescence, given that they were 5 days older, on average, than gynes and males.…”
Section: Differences In Learning and Memory Among Castesmentioning
confidence: 87%
See 4 more Smart Citations
“…DesJardins and Tibbetts (2018) studied P. fuscatus workers and males (drones) over a wide age range (5-30 days) and found that workers were consistently better at facial learning, but the two castes were equally good at colour learning. Similarly, Gong et al (2018) reported that the proportion of honey bee queens (Apis mellifera) exhibiting learning was 5-fold higher than that of honey bee workers at every tested age (5-25 days). Finally, it is possible that workers had decreased learning ability as a result of senescence, given that they were 5 days older, on average, than gynes and males.…”
Section: Differences In Learning and Memory Among Castesmentioning
confidence: 87%
“…In comparison, honey bee (A. mellifera) worker and queen olfactory learning can reach 80% and 90%, respectively, after six learning trials (Gong et al, 2018). Bumble bees (Bombus terrestris) achieved an average of 60% (Riveros and Gronenberg, 2009) or nearly 45% (Stanley et al, 2015) after six learning trials.…”
Section: Caste Learning and Memory In Social Insectsmentioning
confidence: 98%
See 3 more Smart Citations